NITROUS OXIDE EMISSION AND NITROGEN UPTAKE AFFECTED BY SOIL AMENDMENT AND NEMATICIDE IN RAINFED RICE SOILS AT CENTRAL JAVA - Wihardjaka, A.; Tandjung, S. Djalal; Sunarminto, B. Hendro; Sugiharto, Eko (Indonesian Journal of Agricultural Science, 2013)
Rice cultivation is one of the antropogenic sources of nitrous oxide (N2O) emission that is produced by microbiological nitrification-denitrification processes. Incorporating soil amendment in rainfed rice soil attempted to increase soil productivity, while nematicide application aimed to maintain root growth system. Incorporating soil amendment and nematicide application are predicted to suppress N2O production in lowland rice. The objective of this research was to study the interaction of soil organic amendment and nematicide on N2O emission and nitrogen uptake from rainfed lowland rice soils. A field experiment was conducted in rainfed lowland rice soils during 2010/2011 wet season (direct seeded rice) and 2011 dry season (transplanted rice). The 3 x 3 factorial trial was arranged in a randomized completely block design with three replications. The first factor was soil amendment consisted of without rice straw, fresh rice straw and composted rice straw. The second factor was nematicide application consisted of without nematicide, neemcake and carbofuran. Variables measured were N2O flux, rice grain yield and nitrogen uptake. Incorporation of fresh and composted rice straws reduced N2O flux about 49.2% and 59.9% in transplanted rice, and 32.9% and 28.2% in direct seeded rice, respectively. The neemcake application reduced N2O emission about 44-50%, while carbofuran application decreased N2O emission by 23-35%. Neemcake has a good potential as nitrification inhibitor of N2O emission, so the neem trees have a prospect to be cultivated intensively. The reduction of N2O emission was effective in direct seeded rice system with the application of neemcake and fresh rice straw, however, in transplanted rice system it was effective with neemcake and composted rice straw applications.